Measuring the Repurchase Intention of Islamic Retail Stores through the Concepts of Islamic Brand Image, RSQS, and Price Perception - Kalimatulah, Muhamad Riza; Danurwindo, Muhammad Alhakim (UMSurabaya Publishing, 2025)
This study examines the effect of Islamic Brand Image, Retail Service Quality Scale, and Price Perception on Repurchase Intention at Suryamart Islamic Retail Stores. The survey method for data collection in this study uses a questionnaire, where respondents who have purchased more than one purchase. Multiple Linear Regression using SPSS 24 was applied to examine the proposed connections within the analysis model. The results demonstrate that every direct effect in the suggested model has an important impact, with the exception of the connection between RSQS and Repurchase Intention which has no significant effect. The result of this study that Suryamart Islamic Retail Store, Islamic Brand Image positively influences repurchase intention, while Service Quality (RSQS) does not significantly affect repurchase intention. However, Price Perception significantly enhances repurchase intention. When considered simultaneously, all independent variables collectively have a positive influence on repurchase intention